(untitled) (Journal of Organizational Psychology, 2021)
Since their appearance in the middle of the twentieth century in the industrial field, robots are developing in many economic sectors, around the use of artificial intelligence (AI). In this paper, after examining what the concept of robot means today, we analyze the ethical issues that robotics engenders in various sectors of society, starting with industry, through military and police robotics, health, education, household robots and ending with agriculture and the environment. From this analysis, we seek an ethical framework for robotics, which we try to define a problematic from the couple “action and responsibility” of robots.